2010
DOI: 10.1021/bi901956s
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Phosphorylation Modulates Transcription Efficacy through GRIP-1 Recruitment

Abstract: The role of GR phosphorylation in modulating GR-mediated transcription is not fully understood. Here we show that the hGR is rapidly phosphorylated at S211 and S226 in response to the synthetic agonist dexamethasone (dex) in COS-1 cells. Using a triple phosphorylation mutant hGR construct, we demonstrate that phosphorylation at one or more S residues (from S203, S211, and S226) is required for maximal hGR-mediated transcriptional activation on the MMTV promoter in response to dex in COS-1 cells, but that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
2
23
1
Order By: Relevance
“…We have previously shown in COS-1 cells that the most potent GR ligands result in the most rapid GR degradation, with a good correlation shown between ligand-selective GR half-life and transactivation and transrepression efficacy [65]. Consistent with these results, we show that in the End1/E6E7 cells, MPA results in GR turnover typical for a relatively potent GR partial agonist, unlike NET-A and P4 (Figure S4).…”
Section: Resultssupporting
confidence: 89%
“…We have previously shown in COS-1 cells that the most potent GR ligands result in the most rapid GR degradation, with a good correlation shown between ligand-selective GR half-life and transactivation and transrepression efficacy [65]. Consistent with these results, we show that in the End1/E6E7 cells, MPA results in GR turnover typical for a relatively potent GR partial agonist, unlike NET-A and P4 (Figure S4).…”
Section: Resultssupporting
confidence: 89%
“…In control shRNA cells with intact lamina, dexamethasone and shear stress induced significant increases in luciferase activity compared with untreated cells (P Ͻ 0.05), with dexamethasone being a much more potent inducer of GRE-based transcription activation compared with shear stress (P Ͻ 0.05). This finding closely reflects the extent of GFP-GR nuclear localization we assessed quantitatively for control cells and also agrees with our previous report of GRE promoter activation (47) as well as others studies on GRE induction by dexamethasone (6,35,38).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, using MAPK pathway inhibitors, we find that the MAPK pathways ERK, JNK, and p38 do not appear to be involved in TNF␣-induced IL-6 mRNA expression in the absence of DEX in the End1/E6E7 cells, 3 suggesting that MAPKs are not involved in phosphorylation of the unliganded GR at Ser-226 in these cells. Previous results from our laboratory suggest that TNF␣-induced GR phosphorylation of the GR at Ser-226 might be required for the interaction of GRIP-1 with the unliganded GR in End1/E6E7 cells, because we have previously shown that ligand-induced phosphorylation of transfected human GR at one or more serine residues (at positions 211, 226, or 203) is required for GRIP-1 interaction in transfected COS-1 cells (58).…”
Section: Discussionmentioning
confidence: 79%
“…These residues become hyperphosphorylated on ligand binding (57,70). Hyperphosphorylation at one or more of these sites was shown to be required for promoter-specific increased transcriptional activation efficacy (58). As shown in Fig.…”
Section: Discussionmentioning
confidence: 89%